Sport Contact Level Affects Post-Concussion Neurocognitive Performance in Young Athletes. (7th April 2021) - Li, Adam Y; Schupper, Alexander J; Quinones, Addison; Shuman, William H; Ali, Muhammad; Hannah, Theodore C; Durbin, John R; Dreher, Nickolas; Spiera, Zachary; Marayati, Naoum Fares; Gometz, Alex; Lovell, Mark R; et al.
Abstract: Objective: Contact level affects the incidence of sports-related concussion. However, the effects of contact level on injury severity and recovery are less clear and are the focus of this study. Method: Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) for athletes aged 12–22 was performed at baseline ( n = 10, 907 for 7, 058 athletes), after suspected concussion determined by physicians or athletic trainers ( n = 5, 062 for 4, 419 athletes), and during follow-up visits ( n = 3, 264 for 2, 098 athletes). Athletes played contact/collision (CC), limited contact (LC), and noncontact (NC) sports. Injury incidence, severity, and recovery were measured using raw and change from baseline neurocognitive test scores. Comparisons between groups used univariate analysis and multivariable regression controlling for demographic variables. Results: Compared to CC athletes, LC and NC athletes showed decreased suspected concussion incidence. At initial post-injury testing, all neurocognitive test scores were similar between groups except changes from baseline for processing speed were improved for LC compared to CC athletes. Upon follow-up testing, raw neurocognitive scores were better for NC compared to the contact collision athletes in verbal memory, processing speed, total symptom score, migraine cluster, cognitive cluster, and neuropsychiatric cluster scores. For change from baseline scores, LC athletes exhibited better performance on verbal memory, processing speed, and reaction time but also showed higher neuropsychiatric scores than CC athletes. Conclusion: Neurocognitive scores between contact levels were similar at the first post-injury test. However, follow up showed many improved scores and symptoms for limited and NC sports compared to CC sports, which may indicate faster recovery.